2013
DOI: 10.1111/gtc.12088
|View full text |Cite
|
Sign up to set email alerts
|

Ebi alleviates excessive growth signaling through multiple epigenetic functions in Drosophila

Abstract: As multicellular organisms develop, many cells permanently stop dividing and undergo terminal differentiation. The G1 phase of the cell cycle is thought to be the critical decision point for differentiation. Many growth factors, such as epidermal growth factor, are involved in regulating the G1 to S phase transition, and aberrant activation of growth factor signaling is one of the critical causes of tumor formation. Therefore, each cell must have proper mechanisms to suppress inappropriate/excessive activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Importantly, the 14 gene interactions shared by E2F and Cbt (green nodes in Figure 5b) were conspicuous within this group, suggesting a potential coherent core network modulated to promote proliferation (Supplementary Results). Interestingly, our analysis revealed novel interactions that suggest a role for RIO kinases in modulating the function of a transcriptional repressor Ebi, on cell cycle genes (29). We also uncovered several negative cell cycle regulatory loops predicted to limit proliferation that are uniquely engaged when E2F is activated, but not when Cbt is activated.…”
Section: Resultsmentioning
confidence: 95%
“…Importantly, the 14 gene interactions shared by E2F and Cbt (green nodes in Figure 5b) were conspicuous within this group, suggesting a potential coherent core network modulated to promote proliferation (Supplementary Results). Interestingly, our analysis revealed novel interactions that suggest a role for RIO kinases in modulating the function of a transcriptional repressor Ebi, on cell cycle genes (29). We also uncovered several negative cell cycle regulatory loops predicted to limit proliferation that are uniquely engaged when E2F is activated, but not when Cbt is activated.…”
Section: Resultsmentioning
confidence: 95%
“…Inhibition of Psc, one of the major components of PcG, alleviates the reduction of Rbf and rux expression in ebi mutant (Lim et al . ) (Fig. A).…”
Section: Introductionmentioning
confidence: 92%
“…This supports the idea that ebi may act at G1-S in many situations. In terms of cell cycle regulation, recent biochemical analysis revealed that Ebi is forming a complex with RBF1 and inhibits the expression of target genes Rbf/dE2F1 pathway (Lim et al 2013). However, Ebi did not seem to associate with L(3)mbt, suggesting that Ebi/RBF/ E2F is a distinct complex to the dREAM/MMB complex acting in the G1 phase.…”
Section: Ebi Inhibits Aberrant Growth Signalingmentioning
confidence: 99%
See 2 more Smart Citations